Autonomous vehicles and tortious liability: an Islamic perspective - Omoola, Sodiq (Academy of Islamic Studies, University of Malaya, 2018)
The advent of autonomous vehicles, ongoing trials and the likelihood of operational liabilities from operational accident possess some challenges in major legal systems around the world. Existing tort rules seem unsuitable for the regulation of liability in this circumstance. Attempts are being made to seek regulatory reforms which conform to specific legal environment. Expectedly, Muslim countries and Gulf States in particular might want to consider Islamic law principles and legal norms of the societies in formulating applicable laws. This article is a futuristic and proactive attempt to smoothen the legal riddles surrounding autonomous vehicles from an Islamic jurisprudential perspective. The deductive research technique known in Islamic jurisprudence as qiyās (analogical deduction) is adopted to derive new law for new cases. This paper finds that existing Islamic law rules are capable of providing guidepost for the reception of this technology in Muslim countries.